THE INFLUENCE OF EXTRINSIC AND INTRINSIC MOTIVATION ON EMPLOYEE PERFOMANCE AT BANK SULUT MANADO - Mundung, Shintya Ervina Donna; Pangemanan, Sifrid Pangemanan (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Motivation is the basic desire why people do job and performance of employee have a strong related with employee’s motivation and the purpose of this study was to investigate how two variable of motivation (extrinsic and intrinsic motivation) based on Herzberg (1966) that affect employee performance, A conceptual framework based on Human Resources Management, was utilized to form 2 hypotheses predicting the causality between the different variables. After validating the scale to data gathered through questionnaire, regarding 100 respondent employees of Bank Sulut central office Manado, analysis method multiple regressions model used to answer the research problem, whereas a relationship on both motivation and job performance variable it is significant since the theoretical expectations that conclusion are: Extrinsic and intrinsic Motivation influence job performance simultaneously and significantly. Extrinsic motivation influence job performance partially and significantly. Intrinsic motivation influence job performance partially significantly where motivation influence job performance of employee that caused some factors like supervision, training, monitoring, pay, achievement, job security, and relation with work environment. Management of Bank Sulut Manado should concern to understand employee’s need and wants such as provide a comfortable work enviroment and rewarding every task of employee that they can do good job. Keywords: motivation, (extrinsic and intrinsic Motivation), job Performance